Áreas verdes e risco de contaminação parasitológica parques urbanos de Aracaju-SE - Alencar, Claudiene de Jesus (2017)
Urban green areas are considered as icons for environmental conservation. These green areas, in frequency, are concentrated in urban parks, adding positive values to the urban population as a whole as a public space for recreation and leisure. In the recreation areas of these parks there are animals such as dogs and wandering cats and domestic that can contaminate the soil through their fecal waste, and there is the risk of contamination of the regulars. The study sites were: Parque Governador Augusto Franco (Sementeira Park) and Parque Governador José Rollemberg Leite (City Park). Therefore, the objective of this work was to evaluate the index of green areas of the parks, through the analysis of Quickbird satellite images, as well as to identify the parasites with zoonotic potential present in soil and feces found in recreation areas. The results show that the amount of green areas in the City Park increased significantly between 2005 and 2008, while in the Sementeira Park there was a small variation of existing green areas. In the parasitological analysis, we identified the parasites: larvae of Strongyloides stercoralis and eggs of Ancylostoma sp. The three types of samples collected. Therefore, the leisure environment in the analyzed parks can negatively influence the health of society through the transmission of intestinal parasites that are harmful to humans.